Novel antitumour natural products from the phylum Bryozoa - Pejin, Boris; Mojović, Miloš; Savić, Aleksandar G. (Biologia Serbica, 2014)
This review covers literature published from 2003-2012 for natural products from the phylum Bryozoa. The focus is on new antitumour substances, together with details related to the organism sourced. It describes 19 promising bioactives, originating from 7 marine bryozoans. The chemical structures of all highlighted organic compounds are briefly discussed.